2019
DOI: 10.1136/bcr-2019-229541
|View full text |Cite
|
Sign up to set email alerts
|

Pure yolk sac tumour, post-pubertal type, arising from cryptorchid testes

Abstract: Yolk sac tumour (YST), the most common germ cell tumour (GCT) in infants and children, accounts for 80% of GCTs in this age group. 1 It is observed in only 2.4% of adult patients in their pure form since up to 42% of mixed GCTs have some component of the yolk sac. 2 We present a 46-year-old cryptorchid man who presented with complaints of abdominal lump, pain and altered bowel habits since 1 month. CT scan of the abdomen revealed a mass arising from the pelvic cavity with feeders predominantly from the left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…To the best of our efforts, we could find four more reported cases in literature published in English between 2015 and 2019. Janugade et al reported a case of pure YST arising from cryptorchid testis in a 46-year-old male, who presented with a large abdominal lump extending from infra umbilical region to pelvis along with delayed bowel movement [ 6 ]. Murcia et al reported a similar case of pure YST in a 20-year-old male, who also had metastases to the liver, retroperitoneum, and lung [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our efforts, we could find four more reported cases in literature published in English between 2015 and 2019. Janugade et al reported a case of pure YST arising from cryptorchid testis in a 46-year-old male, who presented with a large abdominal lump extending from infra umbilical region to pelvis along with delayed bowel movement [ 6 ]. Murcia et al reported a similar case of pure YST in a 20-year-old male, who also had metastases to the liver, retroperitoneum, and lung [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yolk sac tumors are rare in post-pubertal patients with cryptorchidism. Hemant et.al reported a yolk sac tumor in post-pubertal patients but the testis was intra-abdominal in their case 11 . Our patient histopathological specimen also revealed a yolk sac tumor which is a rare association.…”
Section: Serum Marker Time Reference Rangementioning
confidence: 91%
“…The risk of malignancy decreases when orchidopexy is done before puberty 10 . Seminoma, a testicular germ cell tumor occurs most commonly in cryptorchidism 11 . Yolk sac tumors are rare in post-pubertal patients with cryptorchidism.…”
Section: Serum Marker Time Reference Rangementioning
confidence: 99%
“…The typical perivascular pattern with the characteristic Schiller--Duval bodies was predominantly observed in the conserved areas (Figure 2A). These Schiller-Duval bodies are a hallmark of YST seen in 50%-75% of cases (3). YST that present with only one histological pattern are extremely rare (3).…”
Section: Case Presentationmentioning
confidence: 99%
“…These Schiller-Duval bodies are a hallmark of YST seen in 50%-75% of cases (3). YST that present with only one histological pattern are extremely rare (3).…”
Section: Case Presentationmentioning
confidence: 99%